The Association between Prevalence of JAK2V617F Mutation and Blood Indicies in Groups of Patients with Myeloproliferative Neoplasms in Rasul Akram Hospital - Akram Asghari; Ali Shahriari Ahmadi; Ali Basi; Masood Vkili; Mohsen Razavi; Mohsen Arabi; Majid Niazpour (International Journal of Hematology-Oncology and Stem Cell Research, 2011)
Introduction: Myeloproliferative neoplasms (MPNs) are a group of clonal malignant hematologic disease, where the main and common members are; polycythemia vera (PV), primary myelofibrosis (PMF), and essential thrombocytosis (ET). These group of diseases are able to be transformed into each other. Methods:  This cross sectional study conducted the evaluation of JAK2V161F mutation in DNA in peripheral blood of 91 patients with known or suspected diagnosis of MPNs by Real time PCR method and survey of peripheral blood smear. Result:. Prevalence of JAK2V617F mutation between patients was %58.2 and PV had most common prevalence ratio between other groups. While mean age of patients was 50/9 yr (for 39.6% male and 60.4% female), three patients (equal of %3.3) were atypical presentation and 2 patients die due to malignant transformation. There were significant differences in age, WBC and PLT (in PV) with prevalence of JAK2V617F mutation. These differences were not significant in other group. Discussion:Current study showed a high rate of association between JAK2V617F mutation in patients with PV, ET, PMF in Iranian patients. Therefore, Peripheral blood mutation screening for JAK2 V617F can be incorporated into the initial evaluation of patients suspected to have chronic myeloproliferative neoplasm and used of this test for determining of association between JAK2V617F mutation, treatment of patients with blood indexes and patients of prognosis.